Assessment of radionuclidic impurities in cyclotron produced (99m)Tc - Lebeda, Ondřej; van Lier, Erik J; Štursa, Jan; Ráliš, Jan; Zyuzin, Alexander (Nuclear medicine and biology, 2012)
INTRODUCTION: The commercial viability of cyclotron-produced (99m)Tc as an alternative to generator-produced (99m)Tc depends on several factors. These include: production yield, ease of target processing and recycling of (100)Mo, radiochemical purity, specific activity as well as the presence of other radionuclides, particularly various Tc radioisotopes that cannot be separated chemically and will remain in the final clinical preparation. These Tc radionuclidic impurities are derived from nuclear interactions of the accelerated protons with other stable Mo isotopes present in the enriched (100)Mo target. The aim of our study was to determine experimentally the yields of Tc radioisotopes produced from these stable Mo isotopes as a function of incident beam energy in order to predict radionuclidic purity of (99m)Tc produced in highly enriched (100)Mo targets of known isotopic composition. METHODS: Enriched molybdenum targets of (95)Mo, (96)Mo, (97)Mo, (98)Mo and (100)Mo were prepared by pressing powdered metal into an aluminum target support. The thick targets were bombarded with 10 to 24MeV protons using the external beam line of the U-120M cyclotron of the Nuclear Physics Institute, Řež. The thick target yields of (94)Tc, (94m)Tc, (95)Tc, (95m)Tc, (96m+g)Tc and (97m)Tc were derived from their activities measured by γ spectrometry using a high purity Ge detector. These data were then used to assess the effect of isotopic composition of highly enriched (100)Mo targets on the radionuclidic purity of (99m)Tc as a function of proton beam energy. Estimates were validated by comparison to measured activities of Tc radioisotopes in proton irradiated, highly enriched (100)Mo targets of known isotopic composition. RESULTS: The measured thick target yields of (94)Tc, (94m)Tc, (95)Tc, (95m)Tc, (96m+g)Tc and (97m)Tc correspond well with recently published values calculated via the EMPIRE-3 code. However, the measured yields are more favourable with regard to achievable radionuclidic purity of (99m)Tc. Reliability of the measured thick target yields was demonstrated by comparison of the estimated and measured activities of (94)Tc, (95)Tc, (95m)Tc, and (96m+g)Tc in highly enriched (100)Mo (99%) targets that showed good agreement, with maximum differences within estimated uncertainties. Radioisotopes (94m)Tc and (97m)Tc were not detected in the irradiated (100)Mo targets due to their low activities and measurement conditions; on the other hand we detected small amounts of the short-lived positron emitter (93)Tc (T(½)=2.75h). In addition to (99m)Tc and trace amounts of the various Tc isotopes, significant activities of (96)Nb, (97)Nb and (99)Mo were detected in the irradiated (100)Mo targets. CONCLUSIONS: Radioisotope formation during the proton irradiation of Mo targets prepared from different, enriched stable Mo isotopes provides a useful data base to predict the presence of Tc radionuclidic impurities in (99m)Tc derived from proton irradiated (100)Mo targets of known isotopic composition. The longer-lived Tc isotopes including (94)Tc (T(½)=4.883h), (95)Tc (T(½)=20.0h), (95m)Tc (T(½)=61 d), (96m+g)Tc (T(½)=4.24 d) and (97m)Tc (T(½)=90 d) are of particular concern since they may affect the dosimetry in clinical applications. Our data demonstrate that cyclotron production of (99m)Tc, using highly enriched (100)Mo targets and 19-24MeV incident proton energy, will result in a product of acceptable radionuclidic purity for applications in nuclear medicine.
Keywords: Molybdenum; cyklotrony; časové faktory; Time Factors; Radioisotopes; Radiochemistry; organotechneciové sloučeniny; radiochemie; molybden; radionuklidy; Organotechnetium Compounds; Cyclotrons